Arthroscopic washout of the ankle for septic arthritis in a three-month-old boy - Hagino Tetsuo; Wako Masanori; Ochiai Satoshi (BMC, 2011)
Abstract There is no report of athroscopic treatment for septic arthritis of the ankle in infants. We report a case of successful management of septic arthritis of the ankle in a three-month-old boy by arthroscopic washout. Arthroscopic washout may be a useful treatment for septic arthritis in young infants when performed early after onset.